Polecat : poised for growth - Mitchell, Clare; Sieff, Grant ([London] : SAGE, 2016)
Michael Meltzer is the founder of Zacron Industries CC trading as Polecat, which manufactures and markets a patented clasp and claw device used in shopfitting as well as many other applications. His business, which had shown impressive growth since 2005, was poised to take a further quantum leap forward. The question he asked himself was whether he had the capacity to cope with such extensive expansion? He had started out with a very ambitious business plan, but wondered whether he should be reassessing it in the light of how the business had developed thus far. This text outlines his plans.
Originally Published in: Mitchell, C., & Sieff, G. (2008). Polecat: Poised for Growth. WBS-2008-2. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Polecat (Firm); Business planning -- Case studies; Corporations -- Growth -- Case studies